How to Optimize Tuberculosis Health Education in College Under the New Situation? Based on a Cross-Sectional Study Among Freshmen of a Medical College in Guangxi, China - Wu, Tengyan; He, Huimin; Wei, Suosu; Pan, Jian; Yang, Jingjuan; Huang, Shi; Gan, Shijie; Ye, Chengpeng; Huo, Haiying; Tang, Zhong; Feng, Qiming (Frontiers in Public Health, 2022)
Background China is a country with a high burden of tuberculosis (TB), and students are the high-risk group for TB. The enrollment scale of colleges has increased dramatically due to the advancement of the enrollment expansion system of Chinese colleges. Consequently, this has brought severe challenges to TB prevention and control in colleges. In 2017, a new TB control guide for schools was issued in China, which included the 8 core knowledge of TB. The target of the overall awareness rate on TB among population was “≥85%,” which was proposed by the “13th Five-Year” National TB Control Plan in China. The cognition of the 8 core knowledge of TB in the new guide among college students is crucial to achieve this target, but few studies on this have been reported. Based on the abovementioned new situation and the new guide, this study aimed to investigate and analyze the cognition, attitudes, and health education needs on TB among freshmen of a medical college in Guangxi province, and discuss how to optimize TB health education in colleges in China. Methods A cross-sectional study was conducted among freshmen of a medical college in Guangxi, China. A self-designed questionnaire was used to conduct an on-site questionnaire survey. The data was entered in Epidata 4.4.2.1 and was analyzed using SPSS version 25.0. Including descriptive statistics and t-test, and the criterion for statistically significant difference was p < 0.05. Results A total of 583 freshmen responded to the survey questionnaires. Regarding cognition about the 5 related knowledge of TB, 551 (94.5%) freshmen knew about the predilection site of TB, while 333 (57.1%), 328 (56.4%), 257 (44.1%), and 201 (34.5%) freshmen knew about the pathogen, the policies about free treatment, the designated hospitals, and the World TB Day, respectively. Regarding cognition on the 8 core knowledge of TB, the overall awareness rate among the freshmen is 73.3%(3,420/4,664); the awareness rate of the knowledge that “guarantee adequate sleep, reasonable diet, and strengthen physical exercise can reduce the incidence of TB” among them was the highest at 88.7% (517/583); and the awareness rate of the knowledge that “coughing or sputum expectoration occurred for more than 2 weeks should be suspected of infecting TB and seeking medical treatment in time” among them was the lowest at 47.5% (277/583). Whether students received health education on TB (T = 4.267, p = 0.000) and whether students heard of TB (T = 3.739, p = 0.000) are the main factors of cognition. Five hundred sixty-two (96.4%) and 565 (96.9%) freshmen were willing to learn and tell others about the knowledge of TB, respectively. Three hundred seventy (63.5%.) freshmen, the highest amount, were willing to accept TB health education in the forms of “website, Weibo, and WeChat.” Conclusion The cognition on the 5 related knowledge of TB among freshmen is unbalanced, and the overall awareness rate of the 8 core knowledge of TB among freshmen still needs to be improved. Freshmen who have not heard of TB and have not received TB health education before enrollment are the key intervention groups. It is recommended that institutions make full use of modern multimedia technology, continuously optimize the health education forms, implement precise policies, and strengthen the theoretical and practical health education on TB from the initial entry of freshmen into colleges.